FER1L4/miR‐372/E2F1 works as a ceRNA system to regulate the proliferation and cell cycle of glioma cells. Issue 5 (19th March 2019) - Xia, Liang; Nie, Dekang; Wang, Guangtao; Sun, Caixing; Chen, Gao
Abstract: Long non‐coding RNAs have recently become a key regulatory factor for cancers, whereas FER1L4, a newly discovered long non‐coding RNA, has been mostly studied in gastric carcinoma and colon cancer cases. The functions and molecular mechanism of FER1L4 have been rarely reported in glioma malignant phenotypes. In this study, it was found that the expression of LncRNA FER1L4 is upregulated in high‐grade gliomas than in low‐grade cases and that a high expression of LncRNA FER1L4 predicts poor prognosis of gliomas. Meanwhile, in vitro study suggests that expression of FER1L4 with SiRNA knockdown obviously suppresses cell cycle and proliferation. It is further demonstrated by experiments that the FER1L4 knockdown suppresses growth of in vivo glioma. Besides, it is found in our study that LncRNA FER1L4 expression is positively correlated with E2F1 mRNA expression. After knockdown of FER1L4 expression, E2F1 expression is significantly down‐regulated, whereas the expression of miR‐372 is significantly up‐regulated; the up‐regulation of miR‐372 leads to significant down‐regulation of FER1L4 and E2F1 expression. In addition, it is also found that FER1L4 can be used as competitive endogenous RNA to interact or bind with miR‐371 and thereby up‐regulate E2F1, thus promoting the cycle and proliferation of glioma cells. It may be one of the molecular mechanisms in which FER1L4 plays its oncogene‐like role in gliomas.